Synthesis, carbonic anhydrase inhibition studies and modelling investigations of phthalimide–hydantoin hybrids - Morteza Abdoli; Alessandro Bonardi; Paola Gratteri; Claudiu T. Supuran; Raivis Žalubovskis (Journal of Enzyme Inhibition and Medicinal Chemistry)
A novel series of hydantoins incorporating phthalimides has been synthesised by condensation of activated phthalimides with 1-aminohydantoin and investigated for their inhibitory activity against a panel of human (h) carbonic anhydrase (CA, EC 4.2.1.1): the cytosolic isoforms hCA I, hCA II, and hCA VII, secreted isoform hCA VI, and the transmembrane hCA IX, by a stopped-flow CO2 hydrase assay. Although all newly developed compounds were totally inactive on hCA I and mainly ineffective towards hCA II, they generally exhibited moderate repressing effects on hCA VI, VII, and IX with KIs values in the submicromolar to micromolar ranges. The salts 3a and 3b, followed by derivative 5, displayed the best inhibitory activity of all the evaluated compounds and their binding mode was proposed in silico. These compounds can also be considered interesting starting points for the development of novel pharmacophores for this class of enzyme inhibitors.